1976
DOI: 10.1001/jama.235.9.928
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic complications. Results of the 1974 American Society for Gastrointestinal Endoscopy Survey

Abstract: Esophagogastroduodenoscopy (211,410 examinations) had a complication rate of 1.3/1,000 cases. Duodenoscopy with cannulation was performed 3,884 times and had a complication rate of 21.6/1,000 examinations. Diagnostic coloscopy (25,298 examinations) had a complication rate of 3.4/1,000. Polypectomies during coloscopy (6,124 cases) had a complication rate of 23.3/1,000 cases. Esophageal dilations (13,139 cases) had a complication rate of 4.25 with mercury bougies, and in 9,431 cases metal olives produced a compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
147
1
14

Year Published

1977
1977
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(171 citation statements)
references
References 14 publications
6
147
1
14
Order By: Relevance
“…For example, a study by the American Society for Gastrointestinal Endoscopy involving 25,000 diagnostic colonoscopies reported a complication rate of 0.35%. 4 In another large study, Jentscura et al 5 reported an overall complication rate of 0.4% in 26,695 prospectively registered colonoscopies. The most common complications in adult patients are hemorrhage, preparation-associated complications, adverse effects of sedative medicines, perforation, and bacteremia.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, a study by the American Society for Gastrointestinal Endoscopy involving 25,000 diagnostic colonoscopies reported a complication rate of 0.35%. 4 In another large study, Jentscura et al 5 reported an overall complication rate of 0.4% in 26,695 prospectively registered colonoscopies. The most common complications in adult patients are hemorrhage, preparation-associated complications, adverse effects of sedative medicines, perforation, and bacteremia.…”
Section: Discussionmentioning
confidence: 96%
“…6 Death is a rare complication, occurring in approximately 0.0006% of procedures. 7 Colonoscopy with polypectomy has been reported to have a higher complication rate of up to 3.0%, 4,8 related to postpolypectomy hemorrhage and perforation. 6 Gastrointestinal bleeding has also been reported as the most prevalent complication in adult studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older study in 1974 by American Society for Gastrointestinal Endoscopy Survey showed the overall complication rate was 0.13%. [1] Recent study report of overall complications rate by Mayo Clinic College of Medicine shows decreased overall complications rate as 0.0002 percent for simple diagnostic upper endoscopy. [2] For perforations, esophageal perforation is the most common site of perforation during the upper endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Questions relating to procedure assessment should be included on the board examination and should reflect a general knowledge of this content (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85).…”
Section: Assessment Of Competencymentioning
confidence: 99%